Enhancing Elementary Mathematics Education: The Impact of ICT-Assisted Contextual Learning Models on Learning Outcomes, Cognitive Development, and Student Engagement - Salmaini, Salmaini; Hidayati, Abna; Agusti, Fardatil Aini; Sartono, Sartono; Syafriafdi, Non (Universitas Negeri Padang, 2024)
This research examined how ICT-supported contextual learning approaches impact elementary students' math learning, cognitive growth, and participation. A quasi-experimental study was conducted with 120 fifth-grade students from four schools in Padang, West Sumatra, Indonesia, who were separated into experimental and control groups. The experimental group was taught using contextual learning models assisted by ICT, while the control group received conventional instruction. Standardized mathematics achievement tests, cognitive development assessments, and student engagement and motivation measures were used to collect data. Significant progress was noted in the experimental group for all measures, with substantial effects seen in academic performance (d = 1.46), cognitive growth (d = 1.16), involvement (d = 1.45), and drive (d = 1.47). These results indicate that incorporating ICT into contextual learning can improve elementary math education through better academic results, cognitive growth, and increased student participation and drive. The research adds to the increasing number of studies on incorporating technology in early childhood education and offers insights into educational policies and practices.